Differential Cardiac Effects of Aerobic Interval Training Versus Moderate Continuous Training in a Patient with Schizophrenia: A Case Report - Herbsleb, Marco; Mühlhaus, Tobias; Bär, Karl-Jürgen (Frontiers in Psychiatry, 2014)
Increased cardiovascular morbidity and mortality rates for patients with schizophrenia are reported to contribute to their reduced life expectancy. Common reasons for increased cardiac mortality rates include cigarette smoking, obesity, dyslipidemia, diabetes and poorer health behavior in general. The majority of excess mortality among people with schizophrenia is caused by cardiovascular complications. Reduced vagal activity might be one important mechanism leading to this increased cardiac mortality and has been consistently described in patients and their healthy first-degree relatives. In this case study, we compared two different aerobic exercise regimes in one patient with chronic schizophrenia to investigate their effects on cardiovascular regulation. The patient completed a 6-week period of moderate continuous training followed by a 6-week period of interval training, each regime 2 times per week, on a stationary bicycle. This was followed by a 6-week period of detraining. Primary outcome measures examined heart rate (HR) and heart rate variability (HRV) at rest while secondary measures assessed fitness parameters such as the ventilatory threshold 1 (VT1). We observed that interval training was far more effective than moderate continuous training in increasing HRV, as indicated by RMSSD (improvement to baseline 27% vs. 18%), and reducing resting heart rate (-14% vs. 0%). Improvement in VT1 (21% vs. -1%) was only observed after interval training. Our study provides preliminary data that the type of intervention is highly influential for improving cardiac function in patients with schizophrenia. While cardiovascular function might be influenced by continuous training to some degree, no such effect was present in this patient with schizophrenia. In addition, the beneficial effect of interval training on heart rate regulation vanished completely after a very short period of detraining after the intervention.